Reentrant magnetism at the borderline between long-range antiferromagnetic order and spin-glass behavior in the B -site disordered perovskite system C a2-x S rxFeRu O6 - Naveen, Kumari; Reehuis, Manfred; Adler, Peter; Pattison, Philip; Hoser, Andreas; Mandal, Tapas Kumar; Arjun, U.; Mukharjee, Prashanta K.; Nath, Ramesh; Felser, Claudia; Paul, Avijit Kumar (Physical Review B, 2018)
We report on the coexistence of magnetic order and disorder in the atomically disordered double perovskites Ca2FeRuO6 and CaSrFeRuO6. Powder x-ray and neutron diffraction were used to investigate the crystal structure and magnetic ordering of these oxides. Both compounds are described by the orthorhombic space group Pbnm down to 3 K, where the B site is found to be statistically occupied by Fe3+ and Ru5+ ions. The compound Ca2FeRuO6 shows a G-type antiferromagnetic ordering at TN≈220K, where the moments are aligned parallel to the c axis. The exchange of Ca by Sr suppresses long-range ordering in this system with the consequence that CaSrFeRuO6 shows a diffuse scattering pattern, indicating only the presence of a short-range order of the magnetic moments. Mössbauer measurements additionally reveal the coexistence of a long-range ordered and paramagnetic phase in Ca2FeRuO6, and spin-glass behavior in CaSrFeRuO6. The random occupancy of iron and ruthenium atoms at the B site gives rise to locally varying competing magnetic exchange interactions, which favors the emergence of reentrant magnetism with a spin-glass-like transition at Tf≈87K for Ca2FeRuO6 and a spin-glass transition at ∼65K for CaSrFeRuO6, as evidenced by frequency dependent ac susceptibility measurements. Our results are an interesting example for crossing the borderline between antiferromagnetism and spin-glass behavior in a 3d-4d hybrid perovskite system by modifying the structural distortion associated to the tolerance factor of the perovskite structure rather than changing the concentration of magnetic ions.
CRIS-Team Scopus Importer:2022-04-14